Responding to the Needs of the Most Vulnerable - A Case Study of the Refugee Response on MHM and WASH in the Bidi Bidi Refugee Settlement - Danielsson,Jennelie (2023)
As the number of displaced people is increasing globally, host countries are experiencing difficulties in keeping up with the increasing demands of their growing population. But who is paying the highest price? Through a qualitative approach, this research aims to study the refugee response to Wash, Sanitation, and Hygiene (WASH) as well as Menstrual Hygiene Management (MHM) and how the needs of women and girls are met at the Bidi Bidi Refugee Settlement in northern Uganda. To investigate the refugee response more closely, the following research questions were posed: How do host countries work to develop their refugee response in order to ensure refugee women and girl’s capabilities and agency? What is the current situation in regard to access to WASH and MHM facilities in the Bidi Bidi Refugee Settlement? How do the local Government of Uganda and the NGOs promote work on MHM and WASH in the Bidi Bidi Refugee Settlement? What discourse is present in the data concerning meeting the needs of refugee women and girls? Data was collected through qualitative semi-structured interviews with organizations that work with WASH projects in this particular refugee settlement, as well as through document analysis. The data has been examined through feminist critical discourse analysis, using the theoretical framework of Nussbaum’s Capabilities approach, Egalitarian liberal feminism as well as the Menstrual Concealment Imperative. The results show that there are fewer intervention efforts at the state and regional levels, compared to local levels. NGOs exert more effort in promoting the agency and dignity of women and girls at the local level, in order to achieve adequate WASH and MHM results.
Keywords: Menstrual Hygiene Management; WASH; Refugee response; Capability approach; Equality; Uganda